2002
DOI: 10.4049/jimmunol.169.8.4273
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Ligand Jagged-1 Is Able to Induce Maturation of Monocyte-Derived Human Dendritic Cells

Abstract: Notch receptors play a key role in several cellular processes including differentiation, proliferation, and apoptosis. This study investigated whether the activation of Notch signaling would affect the maturation of dendritic cells (DCs). Direct stimulation of Notch signaling in DCs with a peptide ligand induced DC maturation, similar to LPS: DCs up-regulated maturation markers, produced IL-12, lost endocytosis capacity, and became able to activate allogeneic T cells. Furthermore, coculture of DCs with cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 62 publications
(49 reference statements)
5
83
1
Order By: Relevance
“…Maturation of Human DCs-The maturation of DCs often involves the spectrum of cellular signaling events, including TLR2-dependent activation of NOTCH signaling, which is suggested to play an important role in critical cell fate decisions during DC maturation and subsequent priming of effector T cell responses (37,38). In this regard, we and others have previously shown that TLR2 stimulation leads to up-regulation of NOTCH1 and activation of the NOTCH1 signaling pathway by inducing the formation of a cleavage product of NOTCH1 (NICD) as well as robust activation of Jagged1 expression, a NOTCH1 receptor ligand (39 -44).…”
Section: Notch1-pi3k Signaling Dynamics Integrated Into Signaling Cohmentioning
confidence: 99%
“…Maturation of Human DCs-The maturation of DCs often involves the spectrum of cellular signaling events, including TLR2-dependent activation of NOTCH signaling, which is suggested to play an important role in critical cell fate decisions during DC maturation and subsequent priming of effector T cell responses (37,38). In this regard, we and others have previously shown that TLR2 stimulation leads to up-regulation of NOTCH1 and activation of the NOTCH1 signaling pathway by inducing the formation of a cleavage product of NOTCH1 (NICD) as well as robust activation of Jagged1 expression, a NOTCH1 receptor ligand (39 -44).…”
Section: Notch1-pi3k Signaling Dynamics Integrated Into Signaling Cohmentioning
confidence: 99%
“…Here, we found that HES, the main transcription factor donwstream of Notch, induced a strong transactivation of TGF-ßRII by binding the TGF-βRII promoter through its DNA-binding activity. Taken together, this set of findings is consistent with the conclusion that Notch signaling plays an important role in facilitating TGF-β signaling in effector function and, in turn, TGF-β signaling amplifies these effects by upregulating HES.There is clear evidence that stimulation of APCs (dendritic cells, DCs) via Jagged enhances APC function from the point of view of maturation markers, cytokine production, and differentiation effects on T cells [17]. This raises the question of whether DCs are exposed to Notch ligands in the microenvironments where they reside.…”
supporting
confidence: 86%
“…In addition, it has been shown that Notch signaling may selectively influence T cell differentiation depending, in some studies, on the type of Notch ligand inducing Notch activation (24 -27); this type of Notch signaling function could be considered positive or at least neutral because T cell differentiation occurs within a positive proliferative milieu. Finally, with respect to the effect of Notch signaling on APCs, there is clear evidence that stimulation of APCs (DCs) via Jagged1 enhances APC function from the point of view of maturation markers, cytokine production, and differentiating effects on T cells (43). Overall, therefore, whether one considers the T cell or the APC the main target of Treg suppression, there is no consistent evidence that Notch signaling has the required negative effects that one would expect of a mediator of suppression.…”
Section: Discussionmentioning
confidence: 99%